Napins and cruciferins in rapeseed protein extracts have complementary roles in structuring emulsion-filled gels. (April 2022) - Ntone, Eleni; Kornet, Remco; Venema, Paul; Meinders, Marcel B.J.; van der Linden, Erik; Bitter, Johannes H.; Sagis, Leonard M.C.; Nikiforidis, Constantinos V.
Abstract: We investigated the complementary roles of napins and cruciferins present in a rapeseed protein mixture (RPM) in structuring emulsion-filled gels (EFGs). Napins are small molecular weight albumins with high interfacial activity, while cruciferins are high molecular weight globulins that form gels upon heat-induced gelation. The role of napins is to stabilize the emulsion droplets, while cruciferins, which were previously found to interact with the adsorbed napin interfacial layer, can build the protein gel network around the droplets. The effects of oil concentration (0–30 wt%) and pH (5 and 7) on the rheological and microstructural properties of EFGs were investigated. In the absence of oil, at pH 5, due to low protein solubility, RPM formed a heterogeneous network built of protein aggregates. At pH 7, RPM was more soluble and formed a homogeneous network built of strand-like protein structures with higher gel firmness. In the presence of emulsion droplets, the gel firmness increased, with a more pronounced reinforcement at pH 5 compared to pH 7. The type of gel network did not change by the presence of emulsion droplets neither at pH 5 nor at pH 7, as suggested from confocal microscopy and the unchanged response to large deformation. This implies that oil did not really change the protein network structure. The emulsion droplets, being stiffer than the protein matrix, and being integrated in the structural matrix, increased the gel firmness. This research shows that the presence of two different proteins with complementary roles in a less purified protein extract, provides a single protein ingredient suitable for structuring food emulsion-filled gels. Graphical abstract: Image 1 Highlights: Less purified rapeseed protein extracts contain both napins and cruciferins. Napins and cruciferins had complementary roles in structuring emulsion-filled gels (EFGs). Napins stabilized the emulsion droplets, and cruciferins built the gel network. pH affected the microstructure and gel firmness of the EFGs. Napin-stabilized emulsion droplets reinforced the gel network.